Investigating the Burden of Pseudomonas aeruginosa Infections in COVID Patients and Resistance Profiles in Abbottabad, Pakistan - Sheryar Jamil; Mohammad Ejaz; Sajjad Ali; Sabir Nawaz; Zahid Ahmad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Nosocomial infections are a great menace for hospitalized patients and Pseudomonas aeruginosa has emerged as one of the most potent nosocomial pathogens due to its continuous emanation of multi-drug resistance. Conjointly, P. aeruginosa coinfection is a significant problem in multitudinous infections. The present study aimed to investigate the frequency and antibiotic susceptibility profile of P. aeruginosa, from the specimens isolated from patients from Ayub Teaching Hospital in Abbottabad, Pakistan. In this cross-sectional study, eighty strains of P. aeruginosa were obtained from 200 patients (urine, wounds, and pus samples), using routine microbiological methods, and antibiotic susceptibility testing was performed using the Kirby Bauer disc diffusion method. The majority of isolates (51.25%) were taken from wounds, followed by pus (38%) and urine (27.27%). Of the 80 isolates, 12 originated from individuals who were also infected with the Coronavirus (a 34% coinfection rate). These isolates were sensitive to levofloxacin (80%) and vancomycin (75%) but were resistant to moxifloxacin (80%) and amikacin (69%). P. aeruginosa is found in high frequency in clinical specimens from patients in Abbottabad, and these microorganisms are transiently resistant to routinely given antibiotics, making it critical to utilize anti-Pseudomonas medications correctly. It is concluded that the P. aeruginosa infections and resistance continued to increase owing to various intrinsic and extrinsic factors.